(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Degradation of soil health is a growing concern as both human health and soil microbial community are directly related to this. One of the main hazards to soil deterioration in Bangladesh is soil salinization. In this study, the microbiological status of two commercial biofertilizers, an agricultural soil, and saline soil in Bangladesh were analyzed and compared. Five saline soil samples from various agricultural fields in Satkhira, two commercial biofertilizer samples, and one agricultural soil from Hazi Danesh Agricultural University were collected to carry out this work. The saline soil sample’s physicochemical properties, such as pH and salinity, were examined. Saline soil had a salinity range of 0.17-1.60 ppm and a pH range of 6.20-7.22. Five beneficial bacteria, three types of food-borne pathogen indicators, three types of soil quality indicators, and one plant pathogen indicator bacterium were selected for the microbiological investigation. The microbial status of the five beneficial bacteria was observed; for Rhizobium, the range was not detected to 7.62 log CFU/g, for Azotobacter, it ranged from 3.11 log CFU/g to 5.72 log CFU/g, for phosphate-solubilizing bacteria, it ranged from 3.87 log CFU/g to 4.69 log CFU/g, and for Bacillus, it was not detected to 4.65 log CFU/g. The helpful bacteria Pseudomonas spp. and the plant pathogen inhibitor Trichoderma spp., which are deemed important markers for soil health, were found to be absent in all the samples. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 29-40